PROFILE OF CHILDREN AND ADOLESCENTS WITH DISEASES IN BRAZIL: INTEGRATIVE REVIEW - Martins Costa, Poliana; Kelly da Silva Nascimento, Yohana; Evelly da Silva Olanda, Débora; Carolina Salustino, Maria; Allyson Gomes Ferreira , Jefferson (Health and Society, 2023)
Oral pathologies, such as primary or secondary glomerulars, congenital abnormalities, urinary infection, tubular diseases, are among the most common in children. In children, the progression of the disease can affect the growth of bones, resulting in fragile and anomalous bones, compromising their development. Despite this, it is perceived that the care of children with oral diseases requires professionals, skills and competencies in the identification of priority needs for the planning of care, optimization of conducts and achievement of goals that will promote the restoration of health. In view of the above, the problem of the physical, mental and social domains arises and negatively impacted by the emergence of pathologies, thus, in view of the repercussions caused from the moment children and adolescents receive the diagnosis, the stigma suffered and the interruptions of daily life activities until its outcome, leading to the following questioning : What is the current profile of Brazilian children and adolescents with some nephropathy? The study aims (general): To conduct a survey on the profile of children and adolescents with nephropathies; the study justified by the identification of new contextual elements, which may have been subsidized for the construction of nephrology nursing care in the pediatric s item. This is an integrative review of the literature in which there was analysis and interpretation of articles that met the study proposal.